2021
DOI: 10.1021/acsnano.0c09845
|View full text |Cite
|
Sign up to set email alerts
|

Stable Ti3C2Tx MXene–Boron Nitride Membranes with Low Internal Resistance for Enhanced Salinity Gradient Energy Harvesting

Abstract: Extracting salinity gradient energy through a nanomembrane is an efficient way to obtain clean and renewable energy. However, the membranes with undesirable properties, such as low stability, high internal resistance, and low selectivity, would limit the output performance. Herein, we report two-dimensional (2D) laminar nanochannels in the hybrid Ti3C2T x MXene/boron nitride (MXBN) membrane with excellent stability and reduced internal resistance for enhanced salinity gradient energy harvesting. The internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 60 publications
4
112
0
3
Order By: Relevance
“…Furthermore, in order to output high voltages for powering the electronic devices, a tandem of the GO/ANF membranes stacks is fabricated. 43,44 The output voltages increase linearly with cell numbers (Figure 4d). An ensemble of the composite membranes in series can offer a voltage up to 1.61 V, which can power the electronic devices (inset of Figure 4d).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Furthermore, in order to output high voltages for powering the electronic devices, a tandem of the GO/ANF membranes stacks is fabricated. 43,44 The output voltages increase linearly with cell numbers (Figure 4d). An ensemble of the composite membranes in series can offer a voltage up to 1.61 V, which can power the electronic devices (inset of Figure 4d).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…To improve the power generation performance, an efficient method is to introduce other functional materials (e.g., boron nitride nanosheets, [91] aramid nanofibers [92] ) to the MXene membrane. Zhang et al reported MXene/aramid nanofiber composites membrane for salinity-gradient energy harvesting (Figure 7d), [92] since aramid (also known as Kevlar) is one of the strongest synthetic polymer materials and could form strong hydrogen bond with MXenes due to its rich acylamino groups.…”
Section: Salinity-gradient Energymentioning
confidence: 99%
“…MXene nanosheets have abundant surface groups (such as −F, −OH, and −O) that exhibit outstanding water dispersity and high surface charge density [ 77 , 78 , 79 , 80 ]. To address the challenges of the low stability, high internal resistance, and low selectivity of conventional membranes, Yang et al utilized a Ti 3 C 2 T x MXene/boron nitride (MXBN) membrane for boosting the salinity gradient energy conversion as the addition of BN into a pristine MXene membrane remarkably reduces the internal resistance and thereby, significantly increases the output power density [ 53 ]. Furthermore, Ti 3 C 2 T x MXene membranes have been shown to harness the osmotic energy effectively as their subnanometer ion-selective channels facilitate the preferential cation exchange regulated with the modified surface terminal groups controlled via the salinity gradient.…”
Section: Miniaturized Sge Devicesmentioning
confidence: 99%